(untitled) (American Journal of Technology and Applied Sciences, 2022)
Geotechnical stability is a major concern for the long-term safety and integrity of underground infrastructures such as tunnels, railway stations, mine shafts and hydraulic power chambers. An effective geotechnical monitoring system is able to provide adequate warning to underground personnel prior to any unexpected major geotechnical failure. This paper reviews the conventional geotechnical monitoring sensors and the emerging Fibre Optic Sensing (FOS) techniques, pointing out their unique features and major differences. Recent advances in various FOS based monitoring systems, including Brillouin time domain distributed optical sensors and fibre Bragg grating (FBG) sensors, are investigated through a critical review of the laboratory studies and field applications used for underground geotechnical monitoring. Particular emphasis is given to fibre packaging, temperature compensation, installation methods and instrumentation performance in the underground environment. A detailed discussion of the advantages and limitations of each FOS monitoring system is also presented in this paper.